The Influence of Islamic Capital Market Education and Literacy on Students’ Investment Activity in Digital Sharia Investment Platforms - Maulida Rahma; Nur Ahmadi Bi Rahmani; Yenni Samri Juliati Nasution (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2026)
The purpose of this study is to explore how the level of knowledge about the Islamic capital market influences an individual’s level of activity in investing on Islamic-based investment platforms. Since this study aims to statistically evaluate the relationships among variables, a quantitative approach of the explanatory type was chosen. Students in the Faculty of Islamic Economics and Business at UIN North Sumatra who are currently in their fifth and seventh semesters of the 2024/2025 academic year served as the research subjects. The sample size consisted of 95 respondents. Data analysis was conducted using multiple linear regression with SPSS version 27. The study indicates that Islamic capital market education has a positive impact on students’ investment activity, with a coefficient value of 0.415. However, this effect is not statistically significant because the t-value is 1.726 and the significance level (Sig) reaches 0.088, which is greater than 0.05. On the other hand, Islamic capital market literacy has a positive and statistically significant impact on investment activity (β = 0.717; t = 3.274; Sig = 0.001 < 0.01). In this research model, the most influential variable is literacy, with a standardized beta value of 0.463. Additionally, the results of the simultaneous test (F-test) indicate that knowledge of the Islamic capital market and education together have a significant influence on students’ investment activity (F = 39.997; Sig = 0.000). The R-squared (R²) value of 0.465 indicates that these two factors account for 46.5% of the variation observed.